查看完整版本 : Lim

dodge_viper 2017-8-14 02:23 PM

Lim

求高手幫幫手
做唔到b(i)

費達拿破壞網球 2017-8-14 04:22 PM

Easy,  ln ( 1 +  squrare root of x * sin x) / x = [ ln ( 1 +  squrare root of x * sin x) / ( squrare root of x * sin x)] *  ( squrare root of x * sin x) / x, then the required limit will be the product of these two limit.
Note that in the first one, let y = squrare root of x * sin x,
when x tends to zero, y tends to zero, so by part a, the limit of the first one is 1.
For the second one, (square roof of x * sin x) / x  = square root of (sin x / x), so the limit of this one is 1.
So the reqired answer = 1 * 1 = 1.
頁: [1]
查看完整版本: Lim